UNVEIL THE MEANING OF IBN AL-FARID'S SUFISTIC POETRY USING THE RIFFATERRE'S SEMIOTICS - Choironi, Merry; Nursida, Ida (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
This study was a multidisciplinary study to interpret symbols behind the words in the Sufism poems of Syaraf al-Din Umar Ibn al-Farid in his diwan, Nazm as-Suluk or at-Ta’iyyah al-Kubra and al-Khamriyyah. Ibn al-Farid resembled his love for his God in beautiful, imaginative, and meaningful poetry. This research used the semiotic literary reading method (al-qirâʻah al-simi'iyyah) to unveil the meaning of Ibn al-Fārid's Sufistic poetry which is not only about the genre of Sufism un sich, but also the language and literary styles and levels of imagination through heuristic and hermeneutic interpretations. The beauty of his words with its solid essence is very important to be studied, analyzed and conveyed to the public so that the universe of knowledge is exposed not only about the flow of Sufism un sich, but also language and literary styles and levels of imagination through heuristic and hermeneutic interpretations along with the search for matrices, models and variants in the framework of finding the theme, and the final steps is looking for common ground between the texts and the existing ones through the hypogram.